45th AIAA Aerospace Sciences Meeting and Exhibit 2007
DOI: 10.2514/6.2007-871
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Combined CARS and Interferometric Rayleigh Scattering System

Abstract: This paper describes the characterization of a combined Coherent anti-Stokes Raman Spectroscopy and Interferometric Rayleigh Scattering (CARS-IRS) system by reporting the accuracy and precision of the measurements of temperature, species mole fraction of N 2 , O 2 , and H 2 , and two-components of velocity. A near-adiabatic H 2 -air Hencken burner flame was used to provide known properties for measurements made with the system. The measurement system is also demonstrated in a small-scale Mach 1.6 H 2 -air comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…In these flows, pure, room-temperature fuel is injected into the flow; therefore some regions of the flow will contain only room temperature fuel (hydrogen and or ethylene). The O'Byrne et al CARS system is incapable of making measurements in pure, room temperature hydrogen as discussed in Ref [4]. The O'Byrne et al system is not ideal for measuring combustion of an ethylene-hydrogen fuel mixture because it does not have the capability to measure any of the carbon species present in the flow (CO 2 , C 2 H 4 , and CO).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these flows, pure, room-temperature fuel is injected into the flow; therefore some regions of the flow will contain only room temperature fuel (hydrogen and or ethylene). The O'Byrne et al CARS system is incapable of making measurements in pure, room temperature hydrogen as discussed in Ref [4]. The O'Byrne et al system is not ideal for measuring combustion of an ethylene-hydrogen fuel mixture because it does not have the capability to measure any of the carbon species present in the flow (CO 2 , C 2 H 4 , and CO).…”
Section: Introductionmentioning
confidence: 99%
“…The measurement limit for different CARS systems will vary with the amount of energy used to probe spectral lines and with other attributes of each system such as detector sensitivity and noise, data analysis method, etc. When the O'Byrne et al system was used to make measurements in supersonic combustion flow [4], it showed a measurement limit lower bound of peak height of 3 (square root of the theoretical signal in CARSFT). Square root of the theoretical signal is used in CARSFT because typically species mole fractions scale with the square root of the CARS signal.…”
Section: The Design Of Widecarsmentioning
confidence: 99%
“…Removing spectra that saturate the detector from the analysis, as in Refs. 9,11 , would have neglected those lower temperature shots introducing errors in the average and in the standard deviation estimates. In order to compare experimental and computational results, it is necessary to know the exact location at which the data have been collected.…”
Section: Dp-cars Measurements In the Laboratory-scale Supersonic-cmentioning
confidence: 99%
“…Further improvements were obtained by van Veel 15 thanks to a simultaneous referencing that takes into account the shot-to-shot fluctuations in the modeless dye laser. Use of a modeless dye laser was considered for this instrument, and attempted in the first preliminary measurements taken in the laboratory-scale free jet, 11 but results were unsatisfactory. Figure 9 shows the relative standard deviation computed from 500 single shots measurements in the Hencken burner, and compares it to the results presented in Refs.…”
Section: 41mentioning
confidence: 99%
See 1 more Smart Citation